Strategi Komunikasi Humas BMKG Kota Padang dalam Mitigasi Bencana di Kelurahan Purus Kecamatan Padang Barat - Immanuel Primus Tuaderu; Ria Edlina (CV. ITTC INDONESIA, 2026)
Padang city as a disaster-prone area requires an effective communication strategy to build public awareness of disaster mitigation. This study aims to describe the communication strategy of Public Relations BMKG Padang in disseminating meteorological information for extreme disaster mitigation in West Padang District. The research method used is descriptive qualitative with purposive sampling technique. The research informants consisted of eight people divided into main informants from internal BMKG Padang (Station Chief, Head of Public Relations, Senior Meteorological Staff, Disaster Communications Officers, and Weather Prediction Analysts) and supporting informants from the Purus Village community (Lurah Purus, community leaders/RT heads, and fishermen residents). Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model including data reduction, data presentation, and conclusion drawing. This study uses Risk Communication Theory as a theoretical basis. Through an adaptive and participatory approach, BMKG successfully combines direct communication, digital technology utilization, and collaboration with local community leaders to effectively disseminate weather information. The results show that a strong community information network and deep understanding of local culture contribute to increased public awareness and response to severe weather risks.